Voluntary annual report disclosures by Malaysian multinational corporations / Fathyah Hashim and Norman Mohd Saleh - Hashim, Fathyah; Mohd Saleh, Norman (UPENA, 2007)
Annual reports disclosure of multinational corporations (MNCs) is subject to various domestic as well as international users requirements. Voluntary disclosures act as one of the ways that these MNCs can use to overcome the gap between information provided in annual reports and information expectation by these users. This study examines the relationship between the level of information disclosures and some of the MNCs characteristics. The level of disclosures is based on the amount of the voluntary disclosure information gathered from annual reports of listed MNCs on Bursa Malaysia across six industries. Overall, the results show that level of voluntary information disclosures is positively related to size of the company and the type of audit. Meanwhile, the level of multinationality is significantly related to the level of projected information disclosures. We also found MNCs in particular industries (e.g. construction industry) seem particularly inclined to provide certain information (e.g. summary of history results). Additional tests show that the level of multinationality and the number of countries where the products were exported jointly determine the level of voluntary disclosure in MNCs. Thus, these results indicate that the factors explaining voluntary annual report disclosures differ by the types of voluntary information presented. in annual reports.